Serum CCL22 levels decreased in parallel with disease activity in CCR4‐positive mycosis fungoides treated with mogamulizumab. Issue 6 (17th August 2020) - Ohuchi, Kentaro; Fujimura, Taku; Lyu, Chunbing; Amagai, Ryo; Muto, Yusuke; Aiba, Setsuya
Abstract: Mogamulizumab is a humanized anti‐C‐C chemokine receptor type (CCR)4 antibody that shows cytotoxicity against CCR4+ lymphoma cells via antibody‐dependent cell‐mediated cytotoxicity in advanced cutaneous T cell lymphoma (CTCL) patients. The production levels of ligands for CCR4, that is, Chemokine (C‐C motif) ligand (CCL)17 and CCL22, are important for the assessment of the disease activity in CTCL patients. We evaluated the serum levels of CCL17, CCL19, CCL22, C‐X‐C motif chemokine ligand (CXCL)10, and CXCL13, which are ligands for CCR4, CCR7, CCR4, C‐X‐C Motif Chemokine Receptor (CXCR)3, and CXCR5, respectively, at baseline and 4 weeks after the administration of mogamulizumab in five patients with mycosis fungoides. The serum levels of CCL22 were significantly decreased in patients who responded to mogamulizumab, but no differences were identified in the serum levels of CCL17, CCL19, CXCL10, or CXCL13. Immunofluorescence staining revealed that the majority of CCL22‐producing cells were cluster of differentiation (CD)163+ tumor‐associated macrophages, and they were surrounded by CCR4+ CTCL cells. Our present data suggested that the serum CCL22 level may be a predictive marker of the efficacy of mogamulizumab for the treatment of CCR4+ CTCL.